A AUTOAVALIAÇÃO INSTITUCIONAL E A GESTÃO UNIVERSITÁRIA EM UMA INSTITUIÇÃO FEDERAL - Santana, Josefa Matias (2020)
This study analyses how the Institucional Self-Evaluation is implemented as an instrument of university management in a Federal Institution of Higher Education (Ifes) and as a tool that promotes and induces institucional quality. Institutional Evaluation,